Microteaching Practices based on Multiple Intelligence: A Research and Development of Studentsâ Handbook for English Language Education - Handayani, Sri (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
This research is aimed to (2) identify some problems in microteaching class, (2)find strength and weakness and microteaching class, (3) develop studentsâhandbook based on muliple intelligence. This reasearch and development isconducted towards Microteaching classes in English Language Education. Fourtechniques were applied to collect data, namely interview, observation , FGD andtest. Meanwhile, ADDIE design was implemented in developing students book.The result shows that there are some problems in microteaching class, such asunsufficient laboratory, studentsâ anxiety was contineously increase, lesssuplementary material for students and some other problems. Some weakness wasstill found in implementing microteaching, namely the students book do not suplyreal example in each basic skill. Based on the finding above, the researcher thendeveloped students book for microteaching class based on multiple intelligence toprovide students exploring their inner potential in performing teaching basic skillin microteaching class.Keywords: Microteaching, Multiple Intelligence, research and development